EVALUASI SISWA PADA PROSES KEGIATAN BELAJAR MENGAJAR DALAM PENERAPAN KURIKULUM 2013 DI SMK NEGERI JAKARTA - Iip Apipah; R Eka Murtinugraha; Arris Maulana (Jurnal Pensil : Pendidikan Teknik Sipil, 2016)
This research shows with regard to the evaluation of learning implementation in the vocational school of 1, 26 and 35 of Jakarta particularly the skills of structure image engineering of student grade X in the subject of image technique, which is observed from planning, implementing and lesson result view. It is descriptive evaluative research by using quantitative approach. The model of study choosen is stake evaluation as the researcher has a tendency to understand learning activity which is seen from planning, implementing and lesson result view. The study is carried out in state vocational school of 1, 26, and 35 Jakarta with 118 respondents of student grade X. 36 questionnaires are used for the method of gathering data which had been tested for knowing the valitidy and reliability instrument of the questionnaire in advance. Percentage descriptive analisis is used for the technique of analysis. The aforementioned evidence reveals that the implementation of learning in state vocational school of 1, 26 and 35 Jakarta particularly the skills of structure image engineering of student grade X in the subject of image technique can be seen: The evaluation percentage to lesson plan which include planning of maintaining learning activity, planning of managing study, planning of class management, and planning of student achievements show very good resuly at the average of 80,30%, percentage of learning evaluation includes space, time, learning facility, knowing understanding learning material, using learning source or resource, managing class interaction, assignment implementation, and giving feedback reveals best resuly at the average of 79,83% and learning evaluation indicator include undertaking grading over the course of learning process, grading to the student behavior on learning, and student result which is grouped very good with the average of 80,93%.